Smartphone addiction is more harmful to adolescents than Internet gaming disorder: Divergence in the impact of parenting styles - Li, Zhao-kang; Shi, Li-juan; Cai, Xin-lu (Frontiers in Psychology, 2022)
The adverse effects of smartphone addiction (SPA) and Internet gaming disorder (IGD) on adolescents' mental health have been widely recognized. However, the influence of parenting styles on these high-risk Internet use behaviors of adolescents still remain elusive. Aiming to identify preventable patterns of adolescents with SPA or IGD. This study compared the mental health status between adolescents with smartphone addiction (SPA) and Internet gaming disorder (IGD) and used path analysis to confirm actual effects of parenting styles on SPA and IGD. Participants were enrolled at a junior high school in Hunan Province and a senior high school in Shanxi Province, China (n = 3,049, female (male): 50.5% (49.5%), Mage = 15.68 ± 1.54). All participants reported their socio-demographic characteristics and undertook standardized assessments of SPA, IGD, parenting styles, depression, anxiety, insomnia, self-control, and support utilization. The result showed that high levels of parental care and low levels of parental overprotection benefit adolescents' mental health with SPA and IGD. However, despite having a more positive parenting style, adolescents with only SPA showed more severe mental health problems than adolescents with only IGD. The results further showed that the parenting style of encouraging autonomy might be a protective factor against IGD, but it might instead reinforce SPA indirectly by reducing abilities of support utilization and self-control in whole sample. This study reveals that compared to IGD, SPA which included different kinds of Internet addiction behaviors, was more hazardous for adolescents' mental health. The divergent effects of an autonomy-encouraging parenting style on SPA and IGD may reflect the different impacts of self-control in different types of Internet addiction.